HUBUNGAN ANTARA BEBAN KERJA MENTAL DAN DUKUNGAN KELUARGA TERHADAP STRES KERJA PADA PENGEMUDI OJEK ONLINE KOMUNITAS KBGB SILIWANGI BOGOR TAHUN 2022 - Rizma Aulya, (2022)
Stress at work occurs as a response when a person faces job demands that are not in accordance with his abilities. There are several factors that can cause work stress, namely individual factors and mental workload. Family support is one of the factors that can minimize work stress. The purpose of this study was to determine the relationship between mental workload and family support on work stress. The research method uses quantitative with a cross-sectional approachand uses the Chi Square test. The research sample amounted to 146 using purposive sampling technique. The results of the analysis showed that there was a relationship between mental workload and work stress (p=0.000). However, for the variables of age (p=1,000), gender (p=0,600), last education (p=0,430), marital status (p=0,323), years of service (p=0,751) and family support (p=0,163) did not there is a relationship with work stress. It can be concluded that online motorcycle taxi drivers experience heavy stress and have a heavy mental workload so it is hoped that online motorcycle taxi drivers can manage stress and manage work time according to the energy they have so that stress can be controlled and mental workload can be minimized